Contraposition Between European Universalism and the Right to Intervene - Batanjski, Vera (Zbornik Instituta za kriminološka i sociološka istraživanja, 2014)
European colonialism and the capitalist world economy have common motives and goals; only the arguments to justify intervention and the means of achieving dominance have varied over time. What used to be done, under the pretext of spreading civilisation, development and the spread of Christianity, today is transformed into the spread of democracy and the realisation of human rights. In the pursuit of their own economic growth and development, powerful European states try to establish universal standards all the time. However, these norms are often changed in order to serve their own interests, deviating from the basic democratic principles. In the end, the questions that arise are – Who has the right to intervene? What are the universal values?